The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1104/pp.103.4.1259
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Uptake by Rice Roots (II. Kinetics of 13NH4+ Influx across the Plasmalemma)

Abstract: Short-term influxes of 13NH4+ were measured in intact roots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
208
0
18

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(246 citation statements)
references
References 21 publications
20
208
0
18
Order By: Relevance
“…Similar uptake kinetics have been observed for NO,-influx in barley (Siddiqi et al, 1990) and in the diatom Skeletonema costatum (Serra et al, 1978). Likewise, NH,+ influx in rice is mediated by saturable and linear transport systems (Wang et al, 1993). A dual pattern of K+ influx was also reported in Chlorella (Kannan, 1971), but influx at high [K+I, appeared to occur via a second saturable system.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar uptake kinetics have been observed for NO,-influx in barley (Siddiqi et al, 1990) and in the diatom Skeletonema costatum (Serra et al, 1978). Likewise, NH,+ influx in rice is mediated by saturable and linear transport systems (Wang et al, 1993). A dual pattern of K+ influx was also reported in Chlorella (Kannan, 1971), but influx at high [K+I, appeared to occur via a second saturable system.…”
Section: Discussionsupporting
confidence: 53%
“…In the present study, the influx isotherm for K'(4ZK+ and "Rb+) influx was resolved into a biphasic pattern, with saturable and nonsaturable components. This corresponds to earlier observations describing the patterns of K+ uptake by barley roots (Epstein and Hagen, 1952) and corn roots (Kochian and Lucas, 1982) and more recent studies of NO,-uptake in barley roots (Siddiqi et al, 1990) and NH4+ uptake by rice roots (Wang et al, 1993). The saturable HATS corresponds to Epstein's mechanism 1 (Epstein and Hagen, 1952 (Malhotra and Class, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Although the regulation of NH % + uptake in the root has received less attention than the regulation of NO $ − uptake, it has been shown that the uptake of NH % + can also be regulated via effects on influx. Studies of "$NH % + showed a strong negative down-regulation of influx in response to an increased supply of NH % + to the root (Wang et al, 1993). The signals involved might be unmetabolized NH % + in the root cells or, as in the regulation of NO $ − influx, a reduced N compound translocated from the shoot.…”
Section: Contribution Of Atmospheric N and S Deposition To The N And mentioning
confidence: 99%
“…For evaluating the underlying kinetic constants (i.e. apparent V max and apparent K m ) five different equations describing two to three uptake systems were provisionally fitted to the data (see also Borstlap 1983;Wang et al 1993):…”
Section: Statistical Treatment and Calculationsmentioning
confidence: 99%